STUDY OF THE IMPACT OF PETROLEUM PRODUCTS ON SOIL MICROBIAL FLORA (Experimental biology, 2024)
The study is devoted to assessing the influence of various concentrations of hydrocarbon rocket fuels in the soil, expressed in the quantitative and qualitative composition of the main representatives of the soil biocenosis and enzyme activity. For this purpose, microbiological studies of the qualitative and quantitative composition of soil microflora were carried out in 11 soil samples treated with rocket hydrocarbon fuel grades T-1 and RG-1, with codes K1, T-1-1, T-1-2, T-1 -3, T-1-4, T-1-5, RG-1-1, RG-1-2, RG-1-3, RG-1-4, RG-1-5. As a result of scientific research, in most experimental groups there was a decrease in the number of the main soil representatives of microorganisms, which may be a consequence of exposure to hydrocarbons.
Keywords: rocket fuel, hydrocarbon, soil, fungi, microorganisms, bacteria